(untitled) (Altre Modernità, 2022)
Saidiya Hartman, Perdi la madre. Un viaggio lungo la rotta atlantica degli schiavi (Napoli, Tamu Edizioni, 2021, 336 pp. ISBN 979-12-80195-05-0) di Nicoletta Vallorani